2000
DOI: 10.1111/j.1574-6968.2000.tb08876.x
|View full text |Cite
|
Sign up to set email alerts
|

Class I integrons containing adhfrItrimethoprim resistance gene cassette in aquaticAcinetobacterspp.

Abstract: The presence of antibiotic resistance gene cassettes in class I integrons was investigated in 24 sulfamethoxazole-resistant and -sensitive Acinetobacter isolates derived from two Danish freshwater trout farms. Integrons were detected in five isolates from one of the fish farms, and their inserts were characterised by DNA sequencing. Each isolate contained a dhfrI gene cassette encoding resistance to trimethoprim and an open reading frame orfC of unknown function identical to the content of an integron previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(11 citation statements)
references
References 28 publications
1
9
0
1
Order By: Relevance
“…Thus, they are widely known for their role in acquisition of antibiotic-resistance (Marti, Variatza, & Balcazar, 2014). These two integrons of strain 17ISAe both harboured sul1 gene responsible for resistance to sulfa drugs, similar to previous reports L'Abée-Lund & Sørum, 2001;Petersen et al, 2000;Schmidt, Bruun, Dalsgaard, & Larsen, 2001). of dfrA1-gcuC, a common gene cassette conferring trimethoprim resistance, and sul1 in the integron of strain 17ISAe as described previously (Domingues, da Silva, & Nielsen, 2015;Partridge, Tsafnat, Coiera, & Iredell, 2009).…”
Section: Aeromonassupporting
confidence: 85%
“…Thus, they are widely known for their role in acquisition of antibiotic-resistance (Marti, Variatza, & Balcazar, 2014). These two integrons of strain 17ISAe both harboured sul1 gene responsible for resistance to sulfa drugs, similar to previous reports L'Abée-Lund & Sørum, 2001;Petersen et al, 2000;Schmidt, Bruun, Dalsgaard, & Larsen, 2001). of dfrA1-gcuC, a common gene cassette conferring trimethoprim resistance, and sul1 in the integron of strain 17ISAe as described previously (Domingues, da Silva, & Nielsen, 2015;Partridge, Tsafnat, Coiera, & Iredell, 2009).…”
Section: Aeromonassupporting
confidence: 85%
“…By DNA amplification of the variable region, 43 isolates were found to carry detectable Class 1-related integrons, [36], which may indicate that the dfrA17-aadA5 array can disseminate by self-transferable plasmids in humans or animals. It was believed that the spread of trimethoprim resistance genes in clinical isolates is mostly associated with insertion of gene cassettes into integrons [37]. In our study, trimethoprim and gentamicin resistances were indicated in different dfrA17-aadA5 carrying E. coli isolates.…”
Section: Discussionmentioning
confidence: 84%
“…In some instances, carbapenemase genes, such as bla IMP , bla VIM , bla GIM , or bla SIM , are located within class 1 integrons and lead to carbapenem resistance. Multidrug-resistant Acb complex strains have been known to acquire their antimicrobial resistance genes via class 1 integrons that carry single or multiple gene cassettes [9]. …”
Section: Introductionmentioning
confidence: 99%